In vivo Emergence of Colistin Resistance in Carbapenem-Resistant Klebsiella pneumoniae Mediated by Premature Termination of the mgrB Gene Regulator - Kong, Yingying; Li, Chao; Chen, Hangfei; Zheng, Wei; Sun, Qingyang; Xie, Xinyou; Zhang, Jun; Ruan, Zhi (Frontiers in Microbiology, 2021)
Multidrug-resistant (MDR) Klebsiella pneumoniae is a severe threat to public health worldwide. Worryingly, colistin resistance, one of the last-line antibiotics for the treatment of MDR K. pneumoniae infection, has been increasingly reported. This study aims to investigate the emergence of evolved colistin resistance in a carbapenem-resistant K. pneumoniae isolate during colistin treatment. In this study, a pair of sequential carbapenem-resistant K. pneumoniae isolates obtained from the same patient before and after colistin treatment, named KP1-1 and KP1-2, respectively. Antibiotic susceptibility testing was performed by the microdilution broth method. Whole genome sequencing was performed, and putative gene variations were analyzed in comparison of the genome sequence of both isolates. The bacterial whole genome sequence typing and source tracking analysis were performed by BacWGSTdb 2.0 server. Validation of the role of these variations in colistin resistance was examined by complementation experiments. The association between colistin resistance and the expression level of PhoP/PhoQ signaling system and its regulated genes was evaluated by quantitative real-time PCR (qRT-PCR) assay. Our study indicated that KP1-1 displayed extensively antibiotic resistant trait, but only susceptible to colistin. KP1-2 showed additional resistance to colistin. Both isolates belonged to Sequence Type 11 (ST11). The whole genome sequence analysis uncovered multiple resistance genes and virulence genes in both isolates. No plasmid-mediated mcr genes were found, but genetic variations in five chromosomal genes, especially the Gln30* alteration in MgrB, were detected in colistin-resistant isolate KP1-2. Moreover, only complementation with wild-type mgrB gene restored colistin susceptibility, with colistin MIC decreased from 32 mg/L to 1 mg/L. Expression assays revealed an overexpression of the phoP, phoQ, and pmrD genes in the mgrB-mutated isolate KP1-2 compared to the wild-type isolate KP1-1, confirming the MgrB alterations was responsible for increased expression levels of those genes. This study provides direct in vivo evidence that Gln30* alteration of MgrB is a critical region responsible for colistin resistance in K. pneumoniae clinical strains.